A new open source platform for lowering the barrier for environmental web app development. (November 2016) - Swain, Nathan R.; Christensen, Scott D.; Snow, Alan D.; Dolder, Herman; Espinoza-Dávalos, Gonzalo; Goharian, Erfan; Jones, Norman L.; Nelson, E. James; Ames, Daniel P.; Burian, Steven J.
Abstract: The interactive nature of web applications or "web apps" makes them a well-suited medium for conveying complex scientific concepts to lay audiences and creating decision support tools that harness cutting edge modeling techniques and promote the work of environmental scientists and engineers. Despite this potential, the technical expertise required to develop web apps represents a formidable barrier—even for scientists and engineers who are skilled programmers. This paper describes four hurdles that contribute to this barrier and introduces an approach to overcoming these hurdles. We present an open source implementation of this approach, a development and hosting environment for environmental web apps called Tethys Platform. Several case studies are provided that demonstrates how the approach, as implemented within Tethys Platform, successfully lowers the barrier to web app development in the environmental domain. Highlights: We describe 4 hurdles that deter potential environmental web app development. We introduce an approach that lowers the barrier by addressing each hurdle. Tethys Platform is presented as an implementation of this approach. Tethys Platform includes a suite of FOSS4G software and a software development kit. Several web apps were developed to demonstrate the capabilities of Tethys Platform.